Slavery & Islam - Anggi Azzuhri (American Journal of Islam and Society)
The Euro-American Enlightenment has reformed global moral norms. This reform has provoked humanity to rethink many issues that had been normalized but were nevertheless still moral problems (Hallaq 2019). This  notion applies to many civilizational aspects, but especially the issue of slavery. Some might question why such an immoral institution was seemingly casually practiced in the past without significant opposition. Not only in a particular society, but it seems that the majority—without wishing to generalize—of societies historically accepted slavery as a normal practice. This is the question that provokes Jonathan Brown to reassess the issue of slavery. In particular, this inquiry was provoked following the declaration in 2014 by the Islamic State in Iraq and the Levant / the Islamic State in Iraq and al-Sham (ISIL/ISIS) that the reintroduction of concubinage was legitimate. Following this move, for some the topic of slavery and concubinage came to be identified as a fundamental Islamic teaching.